Pengaruh Terapi Okupasi Terhadap Kemampuan Mengontrol Halusinasi Pada Pasien Gangguan Jiwa di Rumah Sakit Jiwa Prof. Dr. V.L. Ratumbuysang Minahasa - Natasya Alya Bilondatu; Sri Wahyuni; Helly Katuuk (STIKES Columbia Asia Medan, 2023)
Mental disorders are disorders in the mind, behavior, and mood of feelings characterized in the form of a set of symptoms or changes. Hallucinations are one of the symptoms of mental disorders where clients experience sensory changes in perception, feeling sensations in the form of hearing, sight, taste, touch, or smell. This research uses the research method